2017
DOI: 10.1002/lary.26895
|View full text |Cite
|
Sign up to set email alerts
|

Upper esophageal sphincter augmentation reduces pharyngeal reflux in nasogastric tube–fed patients

Abstract: 4. Laryngoscope, 128:1310-1315, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Other studies found an increased UES tone, and a mechanism of aspiration protection has been hypothesized. [25,26]. Our results, which show higher values of Basal UES-CI and UES-RP, might confirm the hypothesis of a protective mechanism of reflux-related aspiration.…”
Section: Discussionsupporting
confidence: 86%
“…Other studies found an increased UES tone, and a mechanism of aspiration protection has been hypothesized. [25,26]. Our results, which show higher values of Basal UES-CI and UES-RP, might confirm the hypothesis of a protective mechanism of reflux-related aspiration.…”
Section: Discussionsupporting
confidence: 86%
“…A retrospective study that compared suspected LPR patients with typical GERD patients has revealed that LPR was characterized by higher UES residual pressure . Findings on UES motility were further supported by the efficacy of UES assist device in the patients with laryngeal symptoms . However, another retrospective study that included 22 esophageal symptom patients, 22 extraesophageal symptom patients, and 44 healthy controls have found that both esophageal symptom patients and extraesophageal symptom patients had lower UES basal pressure and shorter UES length than healthy controls .…”
Section: Discussionmentioning
confidence: 99%
“…8 The device has also been shown to reduce reflux events across the UES in patients receiving long-term nasogastric tube feeds. 9 The feasibility of the UESAD has not been specifically assessed in the LTx population.…”
mentioning
confidence: 99%
“…In addition, significant reductions in salivary pepsin were seen in those with >50% reflux symptom improvement with the UESAD 8 . The device has also been shown to reduce reflux events across the UES in patients receiving long-term nasogastric tube feeds 9 . The feasibility of the UESAD has not been specifically assessed in the LTx population.…”
mentioning
confidence: 99%